2020
DOI: 10.1109/access.2020.3009431
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Dual-Polarized Scalable Antenna Subarray for Compact Millimeter-Wave 5G Base Stations

Abstract: A dual linearly-polarized antenna subarray that operates at 28 GHz and 38 GHz is proposed for fifth generation (5G) base stations. In contrast to earlier millimeter-wave base-station antennas that implement individual single-band antennas, simultaneous realization of dual-band operation can save space and cost. In addition, the proposed subarray depicts dual polarizations, improving signal reliability through polarization diversity. Furthermore, the proposed subarray is scalable and expandable in size and aper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, achieving wideband performance in dual polarization would be an indispensable feature for both mm-Wave and sub-6GHz 5G/6G base stations [67,68]. This would allow for communication at the same frequency band but in orthogonal polarizations, vastly increasing the throughput of the system.…”
Section: Figure 9 Spiral Dipoles With Rectangular Ring Tdf Unit Cell ...mentioning
confidence: 99%
“…Furthermore, achieving wideband performance in dual polarization would be an indispensable feature for both mm-Wave and sub-6GHz 5G/6G base stations [67,68]. This would allow for communication at the same frequency band but in orthogonal polarizations, vastly increasing the throughput of the system.…”
Section: Figure 9 Spiral Dipoles With Rectangular Ring Tdf Unit Cell ...mentioning
confidence: 99%
“…It is experimentally demonstrated that the polarization mismatch becomes a substantial loss factor that heavily affects the overall quality of the wireless link at mmWave frequencies, and dual-polarized phased arrays can provide more reliable Quality of Service (QoS) for mmWave 5G mobile phones than their single-polarized counterparts [4], [5]. Recently, several dualband dual-polarized mmWave antennas have been proposed for 5G applications [6]- [12]. These designs use either stacked patches [6]- [11] or planar dipoles [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several dualband dual-polarized mmWave antennas have been proposed for 5G applications [6]- [12]. These designs use either stacked patches [6]- [11] or planar dipoles [12]. However, their height profiles are in the range of 2 − 4 mm, whereas the typical thickness of the printed circuit boards (PCBs) used in cell phones is around 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the S-band and X-band antennas are mounted in different spaces on the ship mast, the aperture area of the system is increased, resulting in a high RCS. In addition, since the antenna elements are not generally in the form of expandable modules, whenever the array antenna is applied to a differently sized platform, the full array antennas for a new platform must be re-developed [20]. Even in the case of failure of individual antenna elements, the entire system must be repaired or replaced if not modularized.…”
Section: Introductionmentioning
confidence: 99%